Angiogenin promotes angiogenesis via the endonucleolytic decay of miR-141 in colorectal cancer - Chunhua Weng; Haojie Dong; Rongpan Bai; Jinghao Sheng; Guangdi Chen; Kefeng Ding; Weiqiang Lin; Jianghua Chen; Zhengping Xu (Elsevier, 2022)
Mature microRNA (miRNA) decay is a key step in miRNA turnover and gene expression regulation. Angiogenin (ANG), the first human tumor-derived angiogenic protein and also a member of the RNase A superfamily, can promote tumor growth and metastasis by regulating rRNA biogenesis and tiRNA production. However, its effect on miRNA has not been explored. In this study, we find that ANG exclusively downregulates mature miR-141 in human umbilical endothelial cells (HUVECs) via its ribonuclease activity and preferably cleaves single-stranded miR-141 at the A5/C6, U7/G8, and U14/A15 sites via endonucleolytic digestion. By downregulating miR-141, ANG promotes HUVECs proliferation, migration, tube formation, and angiogenesis both in vitro and in vivo. Conversely, downregulated ANG inhibits ANG-mediated miR-141 decay, thus decreasing the angiogenesis process of HUVECs. We also find an inverse correlation between ANG and miR-141 expression in colorectal cancer (CRC) tissues. Our study indicates that ANG regulates CRC progression by disrupting miR-141 and its regulation on angiogenesis-related target genes, not only revealing a new mechanism of ANG action but also newly identifying miR-141 as a substrate of ANG. This study suggests that targeting ANG nuclease activity might be valuable in treating angiogenesis-related diseases through coordinately regulating the metabolism of rRNA, tiRNA, and miRNA.